Leadership Styles and their Influence on Team Collaboration and Innovation in Creative Industries - Wanda Pratiwi; Riska Ariyanti (Generasi Sains Indonesia, 2025)
The current research aims at exploring how specific leadership behaviors affect shared leadership processes and organizational creativity in firms that serve in the creative industry. Precisely, it compares how transformational, transactional, and laissez-faire leadership styles influence the promotion of collaboration and improvement of innovation at the team level. The first research design was quantitative whereby questionnaires were conducted to a total of 150 employees in the creative industries to obtain data. The results reflected good correlation between team collaboration and innovation outcomes, which attracted importance of team collaboration in the development of innovative culture. In some respects, these researches add value to the current understanding by explaining the effects of the behaviors of an individual leader on the level of creativity in working environments where a business operation involving innovation forms a fundamental business activity. The findings confirm that transformational leadership is useful in facilitating cooperation and creativity in the implementation of a change and the evidence that laissez-faire leadership style is not applicable in creative activities. The results are useful to managers working in creative business and have some specific suggestions concerning how managers can take care of a creative organizational culture and promote an effective knowledge sharing.